Highly Luminescent Cesium Lead Halide Perovskite Nanocrystals Stabilized in Glasses for Light‐Emitting Applications. Issue 9 (17th February 2019) - Ye, Ying; Zhang, Wenchao; Zhao, Zhiyong; Wang, Jing; Liu, Chao; Deng, Zhao; Zhao, Xiujian; Han, Jianjun
Abstract: Cesium lead halide (CsPbX3 ) nanocrystals have great potential for photovoltaic and optoelectronic applications, but they are sensitive to oxygen, moisture, and light irradiation. Embedding these CsPbX3 nanocrystals into all‐inorganic amorphous solid matrices such as glass is expected to improve their stability. In this work, CsPbX3 nanocrystals are precipitated in boro‐germanate glasses with tunable composition, absorption, and photoluminescence. Quantum efficiency of CsPbBr3 nanocrystals in glass can be as high as ≈80% and ≈20% for CsPb(Cl/Br)3 and CsPb(Br/I)3 nanocrystals, respectively. Thermo‐ and photostabilities of CsPbX3 nanocrystals in glass are greatly improved due to the inert nature of glasses, and intense laser irradiation‐induced damage to CsPbX3 nanocrystals is recoverable through thermal annealing. With CsPbBr3 nanocrystal‐embedded glass slices, a green light‐emitting device with a luminous efficiency of ≈120 lm W −1 and an external quantum yield of ≈30% is achieved. A white‐light‐emitting device consisting of CsPbBr3 nanocrystals and CsPb(Br/I)3 nanocrystal–embedded glass slices shows luminous efficiency in the range of 50–60 lm W −1 and external quantum yield of 20–25%. The thermo‐ and photostabilities along with the chemical stability of CsPbX3 nanocrystal–embedded glasses are promising materials for photoluminescence related applications. Abstract : Embedding CsPbX3 nanocrystals into glasses improves their thermal and photo‐stability. Photoluminescence quantum yields of 81.1% for X = Br and ≈20% for X = Cl/Br and Br/I are realized. Green (white) light‐emitting devices with luminous efficiencies of 118 (50–60) lm W −1 and external quantum efficiencies of 28.14% (20–25%) are achieved.